SERANGGA-SERANGGA PADA BERBAGAI JENIS BERAS DI PASAR TRADISIONAL KOTA MANADO1) THE INSECTS IN VARIOUS TYPES OF RICE IN TRADITIONAL MARKETS IN MANADO CITY1) - Joice L.A. Kawulusan; Jusuf Manueke; Moulwy Frits Dien (Universitas Sam Ratulangi, 2016)
ABSTRACT study aims to Determine the type and Insect Populations in a variety of commodity rice in the traditional market in the city of Manado from February to May 2015. The study used survey methods in some traditional markets in the city of Manado. Traditional markets as the sample location is Pinasungkulan market at (karombasan), Bersehati market at Calaca, Paal Dua market, and Bahu market. Sampling was done by